Faktor Risiko ISPA pada Balita di Wilayah KerjaPuskesmas Sibela Surakarta - Fitrian Sufianasari; Ismiranti Andarini; Widardo . (Nexus Kedokteran Komunitas, 2012)
Background: Acute respiratory infection (ARIs) continue to be leading cause of acute illnesses and remain the most main cause of infant and young children mortality worldwide, accounting for about two million deaths each year and ranking first among cause of disability-adjusted life-years lost in developing countries. This research aims to get information of risk factors ARIs in children under 5 years old at puskesmas Sibela Surakarta. Methods: This study was a descriptive analytical research using cross sectional approach implemented in April 2012 at puskesmas Sibela Surakarta. Total respondents were 60 people (30 case and 30 controls). Sample was taken by fixed disease sampling whereas children are taken randomly based on inclusion and exclusion criteria that are defined previously. Analysis of data was multivariate with logistic regression, using SPSS program version 17 for windows. Results: Factor proven as risk factor of ARIs were smokers family member (p = 0,047 ;OR 3,728; 95% CI 1,015 13,696) and infected family member (p = 0,001; OR 12,728; 95% CI 2,912 55,626). Factor unproven as risk factors of ARIs were nutritional status (it could not be analyzed) and immunization status (p = 0,902; OR 1,233; 95% CI 0,044 34,285). Conclusions: Factor proven as risk factor of ARIs in children under 5 years were smoker family member and infected family member. Factor unproven as risk factors were nutritional and immunization status. Keywords: ARI, children, risk factor